(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Health Services of Coahuila had not a rabies diagnostic laboratory. It was needed to send samples to Nuevo Leon and InDRE to solve this limitation. On April, 2010, the State Authorities established this laboratory that is placed inside the facilities of the State Laboratory of Public Health. On July, 2010 the laboratory formalized operations with the InDRE. The laboratory has 2 employees: a professional diagnostics specialist and a laboratory technician.